Contarte. a Sistematization of the Reflective Practice Between Teacher and Critical Friend - Angulo-Carmona, M (Universidad Austral de Chile, 2021)
To overcome the obstacles that may show up in the language learning process, especially in children who live in poverty contexts, demands interventions at an early age and teachers with a high reflective capacity. The Systematization of an Experience called Contarte is presented in order to document educational practice at the initial level and add value to collaborative reflection between teacher and critical friend during the teaching-learning process. Findings show that the complexity levels in children’s performance increase as teachers and critical friends continuously feedback in pursuit of the improvement of this educational experience. The reflective effort on the part of the teacher is highlighted as a transforming tool of the unfair reality that does not offer the same opportunities for the development of communicative skills to all children. © 2021. All Rights Reserved.